AIR - Hemat, R. A. S. (Urotext, 2006)
Toxic chemicals in all forms are in the air with the promise of perfect lawns, perfect agriculture, perfect hygienic kitchens, perfect white laundry, perfect office, perfect hospital, perfect travelling, etc. Chemicals saturated air is a source of most diseases-either directly, or by compromising the immune response, or giving the pathogens the evolutionary advantage. This book will guide you through many problems and provide information to help make decisions about the environment. Exploring how to have healthy environment. AIR is based on the extensive international clinical and teaching experience of the author, both in traditional and integrated systems of medical schools.